2017
DOI: 10.1080/03601234.2017.1303322
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pesticides on oxidative stress level in human organism and their activity as an endocrine disruptor

Abstract: Pesticides cause serious environmental and health problems both to humans and animals. The aim of this review is to discuss selected herbicides and fungicides regarding their mode of action and their influence on basic oxidative stress parameters and endocrine disruption properties tested in selected cell cultures in vitro. Because of numerous difficulties which animal studies are subject to, cell cultures are an excellent experimental model reflecting human exposure to different pesticides through all relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 49 publications
0
33
0
1
Order By: Relevance
“…This alteration of dopaminergic pathways might contribute to Parkinson's disease, for which exposure to pesticides is suspected to be a risk factor . In the same way, the in vitro inhibition of steroid hormone transport by pesticides may theoretically participate in their in vivo endocrine disruptive effects, even if in vivo endocrine disruption by most pesticides remains rather incompletely documented to date.…”
Section: Modulation Of Drug Transporter Activity By Pesticidesmentioning
confidence: 99%
“…This alteration of dopaminergic pathways might contribute to Parkinson's disease, for which exposure to pesticides is suspected to be a risk factor . In the same way, the in vitro inhibition of steroid hormone transport by pesticides may theoretically participate in their in vivo endocrine disruptive effects, even if in vivo endocrine disruption by most pesticides remains rather incompletely documented to date.…”
Section: Modulation Of Drug Transporter Activity By Pesticidesmentioning
confidence: 99%
“…OCPs disrupt human metabolism by increasing oxidative stress (OS) levels (9)(10)(11)(12). The loss of balance between the formation of reactive oxygen species (ROS) or nitrogen species (RNS) such as nitric oxide (NO) and the antioxidant defense mechanisms leads to a phenomenon called oxidative stress (OS) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested oxidative stress as one of the mechanisms for the adverse health effects of pesticides exposure; the alteration of the physiological balance bring to the excess of oxidant species, resulting in severe damage to cellular components and macromolecules, especially the DNA [[17], [18], [19], [20], [21]]. Moreover, pesticides exposure may induce the modulation of cells functionality, especially that of the immune system (e.g.…”
Section: Introductionmentioning
confidence: 99%